THE IMPACT OF VISUAL AIDS ON TEACHING VOCABULARY TO YOUNG LEARNERS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article describes how using visual aids are beneficial in teaching vocabulary to young learners. The use of visual aids in teaching can result in varied responses and expressions from young learners due to their diverse educational and cultural background. Nowadays, organizing lesson process effectively, utilizing contemporary methods, especially displaying how visual aids has attracted the attention of young generation and other subjects are placed in first stage. In this regard, several activities are being carried out not only in schools, but also in kindergartens. It is more important to teach foreign language with the help of various visual resources such as picture, cards, diagrams, graphics, postcards, videos, word calendars to boost vocabulary than all of them.